Association between a history of comorbidities and the use of complementary and alternative medicine to prevent COVID-19 - Herrera-Añazco, Percy (2024)
Objective: To evaluate the association between a history of comorbidities and the use of complementary and alternative medicine (CAM) to prevent COVID-19 in Lambayeque, Peru. Material and Methods: Analytical cross-sectional study that used information from the database of the Red Prestacional Lambayeque of the Social Security of Health. The outcome variable was the self-report of having consumed and/or used some type of MAC during the pandemic to prevent COVID-19. The main independent variable was the self-reported history of having any comorbidity. Sociodemographic and clinical confounding variables were included. To assess the association of interest, crude (PRc) and adjusted (PRa) prevalence ratios were calculated using Poisson regression models with robust variances. Results: A total of 243 participants with a history of COVID-19 were surveyed. Most were male (54.7%), and the median age was 29 [25-59] years. 29.2% used CAM to prevent COVID-19. In the adjusted model, a history of comorbidity increased the probability of CAM use (PR: 1.55; 95% CI: 1.05 – 2.28; p: 0.028). Conclusions: A history of comorbidity was associated with a higher probability of CAM consumption during the COVID-19 pandemic in adults to prevent SARS-CoV-2 infection.